Federal and State Expenditures for Working-Age People With Disabilities in Fiscal Year 2014. (September 2019) - Livermore, Gina; Shenk, Marisa; Stapleton, David
Working-age people with disabilities are a large and growing segment of the U.S. population. Expenditures for a variety of federal and state safety-net programs to support these individuals—such as Social Security Disability Insurance, Supplemental Security Income, Medicare, Medicaid, and numerous others—are also growing. However, because expenditures are fragmented across so many programs, the full size and the extent of their growth have been obscured. For this study, we estimated how much the federal government spent on programs in 2014 to support working-age people with disabilities, and we assessed how the size and composition of those expenditures changed during the two 6-year periods preceding 2014. We found that in 2014, the federal government spent US$498 billion on programs to support the working-age population with disabilities, which represents 14% of all federal outlays. States contributed another US$94 billion under federal–state programs. From 2008 to 2014, inflation-adjusted federal expenditures for this population grew by 30%, nearly the same as observed from 2002 to 2008. Expenditures for health care accounted for half of all expenditures in 2014, up from 47% in 2008 and 46% in 2002, and replacing income assistance as the largest expenditure category.